변형 유방촬영술시 통증완화에 따른 요인 분석 - 장명미; Myung Mi Jang; 김화선; Hwa Sun Kim (Journal of the Korean Society of Radiology, 2017)
증가하는 유방암을 발견하고 치료하기 위한 기본검사인 유방 촬영은, 대부분 여성에게 암이나, 방사선 피폭으로 인한 불안을 주게 된다. 게다가 두려운 압박 통증을 주게 되므로, 불안과 통증의 정도를 파악하고, 통증을 완화할 방법을 실험 연구하였다. 임상 경험을 바탕으로 변형된 촬영 방법과 기본 방식의 촬영방법을 각각 비교 분석하여, 그 효과를 평가하는데 목적이 있다. 연구대상은 2017년 2월부터 3월까지 서울대병원운영 서울특별시보라매병원에 유방촬영을 목적으로 내원한, 30대부터 60대 이상까지의 여성 160명이었다. 변형된 유방촬영 방법 80명과, 기존의 유방촬영 방법 80명의 두 그룹으로 나누어 검사하고, 순차적으로 연구대상자 모르게 각각에게 설명하고 설문지를 작성하게 하였다. 연구방법은 첫 번째는 자동페달을 4회 이상 나누어 압박하고, 수동압박을 동시에 이용하며, 자세히 설명하는 태도로 시행하는 변형 방법이다. 두 번째는 기본 방법인 자동 페달 압박 방식만 사용하며, 압박 횟수를 1-3회 이내로 제한하고, 단순히 설명하는 태도로 촬영하였다. 통증 분포의 평균을 살펴보면 실험군(변형촬영방법)은 2.49이고, 대조군(기본촬영방법)은 평균 4.86으로 48.8%로 통증이 감소하는 효과를 나타냈다. 이처럼 변형된 방법으로 촬영한 경우, 실험군이 대조군보다 통증 지수가 낮게 나타났으며, 그 정도는 통계적으로 유의한 결과를 보여주었다 (p<0.001). Mammography, the basic test for finding and treating increased breast cancer, gives the anxiety of cancer and radiation exposure to most women. In addition, it gave very severe compression pain, so we studied the degree of pain and tried to reduce the pain. The purpose of this study is to compare and analyze the modified imaging technique and the basic imaging technique based on clinical experience, respectively. The subjects of this study were 160 women from 30 to 60 years old who visited to Seoul Boramae Hospital operated by Seoul National University Hospital from February to March 2017 for breast screening. Modified 80 persons and 80 persons were divided into two groups, and each group was asked to fill out questionnaires sequentially without knowing the subjects. The first method is a modified method in which an automatic pedal is divided into four or more presses, a manual pressure is used together, and an attitude is described in detail. Secondly, we used only the automatic pedal compression method and press it within 1-3 times. In the mean of the pain distribution, the experimental group (modified method) was 2.49 and the control group (basic method) had an average of 4.86, which showed 48.8% less pain. In this modified method, the pain scores of the experimental group were lower than those of the control group, and the degree of the pain was statistically significant.